Heart rate variability and baroreceptor reflex sensitivity in early- versus late-onset preeclampsia - Weber, Thomas Michael (PLoS One, 2017)
OBJECTIVE: To determine whether there are differences in autonomic nervous system function in early- versus late-onset preeclampsia. METHODS: Matched case-control study. Cases were defined as singleton pregnancies with preeclampsia at < 34(+0) weeks of gestation (early-onset preeclampsia) and ≥ 34(+0) weeks of gestation (late-onset preeclampsia). For each case in each of the preeclampsia subgroups, three „control”uncomplicated singleton pregnancies were matched by maternal age, height, and week of gestation. Blood pressure and heart rate were measured continuously for 30 minutes in each participant. Baroreceptor reflex sensitivity (assessed using sequence technique), time and frequency domain heart rate variability measures, as SDNN, RMSSD, LF(RRI), HF(RRI) and LF/HF(RRI) of R-R intervals, were compared between groups (p<0.05 significant). RESULTS: 24 women with preeclampsia (10 with early-onset and 14 with late-onset preeclampsia) and 72 controls were included in the study. SDNN, RMSSD and HF(RRI) were significantly higher in the late-onset preeclampsia group compared to gestational age matched controls (p = 0.033, p = 0.002 and p = 0.018, respectively). No significant differences in SDNN RMSSD and HF(RRI) between early-onset preeclampsia group and gestational age matched controls were observed (p = 0.304, p = 0.325 and p = 0.824, respectively). Similarly, baroreceptor reflex sensitivity was higher in late-onset preeclampsia compared to controls at ≥ 34 weeks (p = 0.037), but not different between early-onset preeclampsia compared to controls at < 34 weeks (p = 0.50). CONCLUSIONS: Heart rate variability and baroreceptor reflex sensitivity are increased in late- but not early-onset preeclampsia compared to healthy pregnancies. This indicates a better autonomic nervous system mediated adaptation to preeclampsia related cardiovascular changes in late-onset disease.